Eco-friendly synthesis of magnetite based on tea dregs (Fe3O4-TD) for methylene blue adsorbent from simulation waste - Rahmayanti, Maya; Yahdiyani, Atika; Afifah, Ika Qurrotul (Communications in Science and Technology, 2022)
Methylene blue is a popular dye used in the batik industry; however, it potentially causes environmental problems in view of the residual MB content in the liquid waste, which is difficult to naturally degrade. This study aimed to synthesize Fe3O4-TD using tea dregs from household waste and its application as an adsorbent for methylene blue dye. The synthesis was carried out using the reverse co-precipitation method with water as a solvent at room temperature. Fe3O4-TD characterization using FTIR, XRD, and PSA. The adsorption of methylene blue (MB) on Fe3O4-TD was studied at various pH MB, reaction time, and concentration MB to determine the kinetic model and MB adsorption isotherm on Fe3O4-TD and the interactions that occur between MB and Fe3O4-TD. FTIR spectra and X-Ray diffractogram showed that the magnetite formed in a pure state did not mix with other iron oxides. The crystal and particle size of Fe3O4-TD is 18.92 nm and 26.70 µm, respectively. MB adsorption on Fe3O4-TD occurred well at pH > 3 and followed the Ho' pseudo-second-order kinetics model and the Freundlich isotherm model. The interactions between MB and Fe3O4-TD through electrostatic interactions, hydrogen bonds, and phi-phi interactions.